Interpretasi Hadits Nabi Larangan Dua Akad Dalam Satu Transaksi - Yuliani, Marifah (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2021)
This study aims to interpret the hadith "صَفْقَتَيْنِ فِي صَفْقَةٍ". The method used is the method of criticism of sanad, criticism of matan, see the status and quality of the hadith, and analysis using textual, contextual and intercontextual interpretations. The hadith صَفْقَتَيْنِ فِي صَفْقَةٍ cannot be understood through textual because the purpose of this hadith is explained in another hadith. One of the prohibited buying and selling regarding this hadith is the difference between the purchase price of cash and credit. For example, buying and selling socks at 2 prices, ten thousand rupiah in cash or fifteen thousand rupiah in credit. The buyer has received the goods but there is no certainty whether the cash agreement or credit agreement. This is forbidden because it contains gharar (uncertainty, in this case the method of payment). Gharar / taghrir is forbidden in Islam because it causes one party to suffer a loss while the other party gets benefits, so that the purpose of buying and selling is the same willing between the seller and the buyer is not achieved. The solution that is allowed in buying and selling is the certainty of the buyer, choosing the method of payment in cash or credit (so avoiding gharar).